2021
DOI: 10.1002/adma.202100566
|View full text |Cite
|
Sign up to set email alerts
|

An Intrinsically Micro‐/Nanostructured Pollen Substrate with Tunable Optical Properties for Optoelectronic Applications

Abstract: There is broad interest in developing photonically active substrates from naturally abundant, minimally processed materials that can help to overcome the environmental challenges of synthetic plastic substrates while also gaining inspiration from biological design principles. To date, most efforts have focused on rationally engineering the micro‐ and nanoscale structural properties of cellulose‐based materials by tuning fibril and fiber dimensions and packing along with chemical modifications, while there is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Scanning electron microscopy (SEM) images showed that the toner printed on the pollen paper fused and formed a coating layer with discrete pits, whose micromorphology depended on the print setup (Figure S12a,b, Supporting Information). [ 32 ] Because of the unique intrinsic microstructure of the pollen paper, with its surface roughness, [ 33 ] the fused toner was conformally deposited along the contour of the paper surface (Figure S12c,d, Supporting Information), ensuring a tight bond between the toner and pollen paper with superior resistance to separation (Figure S13, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) images showed that the toner printed on the pollen paper fused and formed a coating layer with discrete pits, whose micromorphology depended on the print setup (Figure S12a,b, Supporting Information). [ 32 ] Because of the unique intrinsic microstructure of the pollen paper, with its surface roughness, [ 33 ] the fused toner was conformally deposited along the contour of the paper surface (Figure S12c,d, Supporting Information), ensuring a tight bond between the toner and pollen paper with superior resistance to separation (Figure S13, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…12d). 118 Compared to conventional photovoltaic substrates, the pollen material can achieve versatile and tunable functional properties without complex processing, which makes it an excellent candidate for new environmentally friendly photovoltaic device components. 114 Copyright 2022, Advanced Materials Technologies.…”
Section: Flexible Electronicsmentioning
confidence: 99%
“…(d) Schematic illustration and the cross-sectional SEM image of the flexible perovskite solar cell on the nonpressed pollen substrate. Reproduced with permission 118. Copyright 2021, Advanced Materials.…”
mentioning
confidence: 99%
“…[36][37][38] This unique process uses a pollen-based soft microgel as the building block for natural materials with tunable mechanical, physical, and functional properties. [39][40][41][42] In this study, we demonstrate the feasibility of fabricating and deploying pollen-based materials as unique natural biopolymer substrates for flexible and stretchable electronics. By treating natural pollen with potassium hydroxide (KOH), cellular materials including lipids and proteins can be eliminated, and the hard pollen can be transformed into a non-allergenic, hollow, and soft microgel.…”
Section: Introductionmentioning
confidence: 99%